Physıologıcal response of Apocynum venetum L. seedlıngs under osmotıc stress - Zhao, Hua; Dai, Huiping (Bangladesh Journal of Botany, 2018)
Effects of drought stress were induced by polyethylene glycol (PEG-6000) (10, 20, and 30% ) for 2, 4, 6 and 8 days in Apocynum venetum L. seedlings with the potting method. The results showed that PEG significantly increased the activities of glutathione reductase (GR), superoxide dismutase (SOD), ascorbate peroxidase (APX), and the contents of electrolyte leakage rates, MDA, proline and soluble sugar were increased from 30% PEG. Thus, it was indicated that the application of exogenous 30% PEG induced oxidative damage by enhancing antioxidant defense systems.